An Updated Meta-Analysis of DOACs vs. VKAs in Atrial Fibrillation Patients With Bioprosthetic Heart Valve - Cao, Yalin; Zheng, Yuxiang; Li, Siyuan; Liu, Fuwei; Xue, Zhengbiao; Yin, Kang; Luo, Jun (Frontiers in Cardiovascular Medicine, 2022)
Current guidelines recommend the utilization of direct-acting oral anticoagulants (DOACs) in patients with non-valvular atrial fibrillation (AF). However, the optimal anticoagulation strategy for AF patients with bioprosthetic heart valves (BPHV) remains controversial. Therefore, we conducted this meta-analysis to explore the effect of DOACs versus vitamin K antagonists (VKAs) in this population. Methods: We systematically searched the PubMed and Embase databases until November 2021 for studies reporting the effect of DOACs versus VKAs in AF patients with BPHV. Adjusted risk ratios (RRs) and 95% confidence intervals (CIs) were pooled using the random-effects model with an inverse variance method. Results: We selected four randomized clinical trials and seven observational studies (2236 DOAC- and 6403 VKAs-users). Regarding the effectiveness outcomes, there were no significant differences between DOACs and VKAs in stroke or systemic embolism (RR=0.74, 95%CI: 0.50-1.08), ischemic stroke(RR=1.08, 95%CI: 0.76-1.55), all-cause death (RR=0.98, 95%CI: 0.86-1.12), and cardiovascular death (RR=0.85, 95%CI: 0.40-1.80). In terms of the safety outcomes, DOACs was associated with lower risks of major bleeding (RR=0.70, 95%CI: 0.59-0.82) and intracranial bleeding (RR=0.42, 95%CI: 0.26-0.70), but the risks of gastrointestinal bleeding (RR=0.85, 95%CI: 0.65-1.13) and any bleeding (RR=0.92, 95%CI: 0.73-1.17) are not significantly different when compared with VKAs. The subgroup analysis with follow-up as a covariate revealed that the DOACs had lower risks of SSE (RR=0.59, 95%CI: 0.37-0.94) and major bleeding (RR=0.69, 95%CI: 0.58-0.81) in patients with a mean follow-up of more than 24 months, but no statistical differences were found in patients with the follow-up less than 24 months (SSE: RR=1.10, 95%CI: 0.92-1.32; major bleeding: RR=0.91, 95%CI: 0.42-2.01). Conclusions: In AF with BPHV, patients on DOACs experienced a reduced risk of major bleeding and intracranial bleeding; and had a similar risk of stroke, cardiovascular death, and all-cause mortality when compared to VKAs.